Indigenous knowledge of seasonal weather forecasting: a case study in six regions of Uganda - Okonya, J.; Kroschel, Jürgen (Scientific Research Publishing, Inc., 2013)
Indigenous knowledge of seasonal weather forecasting could be useful in decision making at village level to best exploit the seasonal distribution of rainfall in order to increase or stabilize crop yields. We examined existing indigenous knowledge by interviewing 192 households in six regions of Uganda. Twenty one distinctive indicators were mentioned by local communities for forecasting the start of the dry season, but only few of these indicators were more consistently and frequently used in the different districts. These included the appearance of bush crickets (Ruspolia baileyi Otte), winds blowing from the east to the west, the appearance and movement of migratory birds such as cattle egrets (Bubulcus ibis Linnaeus), and calling by the Bateleur eagle (Terathopius ecaudatus Lesson). For prediction of the start of the rainy season, 22 indicators were mentioned and these included winds blowing from the west to the east, cuckoo birds (Cuculiformes: Cuculidae) start to call, and winged African termite (Coptotermes formosanus Shiraki) swarms leave their nests. Predictors of rain in the following days included presence of red clouds in the morning. Together with the meteorological forecasts, traditional indicators could be very useful in rain forecasting and improving the timing of agricultural activities.